2004
DOI: 10.1161/01.cir.0000138392.68841.d3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Predictors of Aortic Root Dilation and Aortic Regurgitation After Arterial Switch Operation

Abstract: Background-Neo-aortic root dilation (ARD) and neo-aortic regurgitation (AR) may be progressive after arterial switch operation (ASO) for d-loop transposition of the great arteries (dTGA). We sought to identify predictors of ARD and AR after ASO. Methods and Results-335 patients were identified who underwent ASO for dTGA with intact ventricular septum or ventricular septal defect (VSD), including double-outlet right ventricle (DORV), before 2001 with at least 1 postoperative echocardiogram at our institution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 15 publications
8
101
3
1
Order By: Relevance
“…It is now clear that a certain percentage of patients will need further reintervention/ reoperation [10,15,[17][18][19], which in the majority of patients is on the right side of the heart, for neopulmonary stenosis either at the anastomosis site or at the pulmonary artery bifurcation (after the LeCompte maneuver) [7,9,10]. Less commonly, reoperations involve the left side of the heart, such as the neoaortic valve, the aortic root, the subaortic area, and the coronary arteries [4,5,9].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clear that a certain percentage of patients will need further reintervention/ reoperation [10,15,[17][18][19], which in the majority of patients is on the right side of the heart, for neopulmonary stenosis either at the anastomosis site or at the pulmonary artery bifurcation (after the LeCompte maneuver) [7,9,10]. Less commonly, reoperations involve the left side of the heart, such as the neoaortic valve, the aortic root, the subaortic area, and the coronary arteries [4,5,9].…”
Section: Commentmentioning
confidence: 99%
“…Conversely, the progression of the degree of neoaortic valve insufficiency rarely occurs during the first 10 to 15 years after ASO, but it was found that it increases significantly later, and this is associated with the degree of postoperative neoaortic valve insufficiency at discharge soon after ASO [14,20,21]. Anatomic causes identified to be responsible for aortic root dilatation and neoaortic valve insufficiency included the presence of a ventricular septal defect and aortic/pulmonary mismatch and the postoperative geometry of the aortic root [19]. In addition, previous pulmonary artery banding and coronary reimplantation techniques (ie, the trapdoor technique) were also previously identified as significant risks for aortic root dilatation and neoaortic valve insufficiency [14,12].…”
Section: Commentmentioning
confidence: 99%
“…Significant neoaortic root dilatation and neoaortic valve regurgitation may develop over time, in part related to older age at the time of ASO or to an associated VSD with previous pulmonary artery banding. 568 …”
Section: Clinical Features and Evaluation Of Dextro-transposition Of mentioning
confidence: 99%
“…The natural history of neoaortic root dilation in this setting is unclear. Previous studies have demonstrated data, with reports of the indexed neo-aortic root dimensions progressively increasing over time [17]. Neo-aortic valve regurgitation may also be an important late complication, and although uncommon, the need for aortic valve repair or replacement has now been reported in several series late after ASO [18].…”
Section: Discussionmentioning
confidence: 98%